A thin line between 'us' and 'the other' : multiculturalism and representation of North Korean defectors in South Korean cinema - Yoo, Hyerim (2020)
More and more immigrants have entered South Korean society in the recent few years. With the demographic changes in South Korean society, multiculturalism is getting more and more attention in the society. Cinema, as one of the main media outlets in South Korean society has also been interested in representing multicultural population in numerous films, specifically in independent films. Contemporary South Korean cinema has told stories about struggles of newly arrived immigrants. However, due the the characteristic of South Korean multiculturalism which mainly focus on ethnically different migrant groups, ethnic Koreans including North Korean defectors have been excluded from the multicultural discourses in South Korean society. In this sense, the present study explores media representation of North Korean defectors as ’the Other’ with South Korean multiculturalism. The aim of this this is 1) To figure out how North Korean defectors who are ethnic Koreans are othered in the multicultural South Korean society, 2) To analyze North Korean defectors’ representation issues embedded in the media, 3) To encourage other researchers to conduct studies about this topic in the perspective of multiculturalism. In order to accomplish the aims, Critical Discourse Analysis was imployed for the analysis method. With the use of CDA, cinematic texts of the film, The Journals of Musan were analyzed. The results showed strong criticism of capitalist South Korean society, placelessness of North Korean defectors and limited representation of North Korean defectors being incompetent, innocent and illegal. To conclude, it is important to include ethnic Koreans within South Korean multicultural discourses, not to other minority groups in the society, and to diversify representations of the Other.